Production and Quality Evaluation of Herbal Tea Mixtures from Phyllanthus debilis, Osbeckia octandra, and Artocarpus heterophyllus Leaves - P. Gayani I. Dias; R.A. Upul J. Marapana; R.M. Udaya S.K. Rathnayaka (Sumatera Medical Journal, 2023)
Background: This study explored the acceptability and quality of herbal tea blends formulated using powdered leaves of Phyllanthus debilis, Osbeckia octandra, and Artrocarpus heterophyllus. Herbal teas are widely consumed for their health benefits, and optimizing their composition is essential for consumer satisfaction and market viability. Objectives: The aim was to evaluate sensory attributes, nutrient content, tea quality parameters, and safety aspects of different herbal tea formulations. Methods: Tea samples were prepared in various proportions and evaluated by thirty untrained panelists for sensory preferences. Proximate composition, quality indicators, and microbial counts were assessed using AOAC and ISO standard methods. Mineral content was determined via atomic absorption spectrophotometry. Results: Dark-colored tea samples were preferred, with a strong positive correlation between redness and color preference. However, bitterness and astringency negatively affected overall acceptability. The A. heterophyllus tea had the highest overall acceptability, while teas containing P. debilis had the highest color preference. Nutrient analysis showed rich content, though crude fiber and moisture exceeded ideal limits. All microbial counts and heavy metal levels were within safety standards. Conclusion: Combining these herbal leaves can improve both acceptability and quality of herbal infusions. With further refinement, these blends hold strong commercial potential.